2013
DOI: 10.1158/0008-5472.can-12-2064
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-2 Functions as a Tie2 Agonist in Tumor Models, Where It Limits the Effects of VEGF Inhibition

Abstract: The angiopoietins Ang1 (ANGPT1) and Ang2 (ANGPT2) are secreted factors that bind to the endothelial cellspecific receptor tyrosine kinase Tie2 (TEK) and regulate angiogenesis. Ang1 activates Tie2 to promote blood vessel maturation and stabilization. In contrast, Ang2, which is highly expressed by tumor endothelial cells, is thought to inhibit Tie2 activity and destabilize blood vessels, thereby facilitating VEGF-dependent vessel growth. Here, we show that the inhibition of tumor xenograft growth caused by an A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
150
5
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(165 citation statements)
references
References 47 publications
8
150
5
2
Order By: Relevance
“…Shyu et al (2003) reported that the variations in the expression of Ang2 and Tie2 have a temporal pattern with a maximal increase at 24-48 h after reperfusion. The most validated model explaining Ang2 role in tumors and in cardiac capillary density modifications proposes that Ang2 inhibits Tie2 signaling facilitating VEGF-dependent angiogenesis (Maisonpierre et al 1997, Daly et al 2013. As in our model Ang2 expression was not associated with VEGF expression, our findings do not suggest that Ang2 and VEGF act in concert in response to T 3 infusion in I/R.…”
Section: Figurecontrasting
confidence: 59%
See 2 more Smart Citations
“…Shyu et al (2003) reported that the variations in the expression of Ang2 and Tie2 have a temporal pattern with a maximal increase at 24-48 h after reperfusion. The most validated model explaining Ang2 role in tumors and in cardiac capillary density modifications proposes that Ang2 inhibits Tie2 signaling facilitating VEGF-dependent angiogenesis (Maisonpierre et al 1997, Daly et al 2013. As in our model Ang2 expression was not associated with VEGF expression, our findings do not suggest that Ang2 and VEGF act in concert in response to T 3 infusion in I/R.…”
Section: Figurecontrasting
confidence: 59%
“…More precisely, Ang2 is present at low levels in resting endothelial cells, whereas it is increased in the endothelial cells of remodeling blood vessels (Maisonpierre et al 1997, Daly et al 2013. Furthermore, Ang2 expression is upregulated in a wide range of human cancers , Daly et al 2013) and Tie2 receptor is broadly expressed in the endothelium of quiescent adult vasculature.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Receptor tyrosine kinases act as potent oncoproteins and are abnormally expressed in a number of cancer types, including gliomas (5). Angiopoietin-1 (Ang1) receptor (TEK, also known as Tie2) is a receptor tyrosine kinase that was identified as an endothelial-cell-specific receptor with a critical role in the modulation of vasculogenesis and remodeling (6). Tie2 expression occurs, and is partially maintained, during differentiation in human neural stem cells (7), but not in mature neurons (8).…”
Section: Introductionmentioning
confidence: 99%
“…Ang1 is a secreted ligand for Tie2 that maintains vascular plasticity, perturbations in which can contribute to abnormal vascular growth (4). Daly et al (6) revealed that Ang2 functions as a Tie2 agonist in tumor models, limiting the effects of VEGF inhibition (6). Mitsutake et al (13) revealed that Tie-2 and its ligand Ang1 were expressed in benign and malignant human thyroid tumor cells, as well as in hyperplastic regions of adenomatous goiter (13).…”
Section: Introductionmentioning
confidence: 99%